1985
DOI: 10.1111/j.1532-5415.1985.tb07134.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying and Small‐bowel Transit Rate in the Elderly

Abstract: Gastric emptying of liquid and small bowel transit in a group of elderly patients (mean age 79 years) was studied, with the elderly subjects compared to two groups of young controls. In 14 elderly patients, the initial rate of gastric emptying was significantly higher than in 14 young controls: the five-minute volume was 159 +/- 30 ml (mean +/- SEM) in the elderly patients and 294 +/- 22 ml in the young controls (p less than 0.005). The two groups' gastric emptying rates after five minutes were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…It has been shown that the rate of gastric emptying of liquids and solids decreases with age 29) ; however, intestinal motility is not altered and pancreatic secretion slightly decreases with age 30) . In addition, LPL activity has been reported to decrease with age 31) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the rate of gastric emptying of liquids and solids decreases with age 29) ; however, intestinal motility is not altered and pancreatic secretion slightly decreases with age 30) . In addition, LPL activity has been reported to decrease with age 31) .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to investigate the process of postprandial plasma retinyl ester clearance, we infused retinyl ester-rich plasma to a selected group of young adult and elderly subjects and determined the subsequent rate ofplasma retinyl ester decay. These 52 2/2 * Taken from 14-h overnight fasting blood. $ Decay curves were constructed as described in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…time was unaltered by increasing age (50)(51)(52) The absorption of vitamin A in oral dose or feeding studies also depends on the resistance of the diffusion barrier at the intestinal cell surface. Hollander and Morgan (58) have shown in rats that the rate of uptake of radiolabeled vitamin A by perfused intestinal segments increases with advancing age, and have suggested that this finding is due to an age-related decrease in the resistance of the diffusion barrier at the intestinal cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the gastric emptying of liquids and solids decreases with age 10 , but intestinal motility is not altered with age 11 . Pancreatic secretion slightly decreases with age 12 .…”
Section: Discussionmentioning
confidence: 99%